Суб'єкти протидії нелегальній (незаконній) міграції в Україні - Новіченко, А. В.; Novichenko, A. V. (Наше право. - 2020. - № 2. - С. 99-105, 2020)
Наголошено, що на сьогодні реалізація державної політики у сфері незаконної міграції має багато прогалин. Україна, як держава, зіткнулася з відсутністю ефективної системи правового регулювання міграційних процесів, які створюють загрозу в країні, сприяють зростанню злочинності та утворенню організованих злочинних груп, обумовлюють загострення соціальної напруги в суспільстві. Визначено завдання та функції суб’єктів протидії нелегальній міграції. Досліджено питання видів суб’єктів протидії нелегальній міграції в Україні, їх функції і взаємна співпраця.

The implementation of the state national security policy today is one of the main problems in Ukraine. Illegal migration poses a serious threat to Ukraine’s national security and stability in society. Ukraine, as a state, is faced with the lack of an effective system of legal regulation of migration processes that threaten the national security of the country, contribute to the growth of crime and the formation of organized criminal groups, exacerbate social tensions in society. Therefore, the question of defi ning the tasks and functions of the subjects of combating illegal migration arises. The issues of types of subjects of counteraction to illegal migration in Ukraine and their functions and mutual cooperation are studied. Direct control over the deployment of migration fl ows is carried out on the basis of national legislation, which is fundamental in shaping the migration policy of the state. In addition to the creation of a national legal framework, the key to the successful implementation of state migration policy is the formation of institutions responsible for managing external labor migration; proper staffi ng of specialized public authorities; ensuring a suffi cient material and fi nancial base for regulating migration; approval of scientifi c and information support of the management process. State regulation of labor migration is seen as a purposeful activity of state executive bodies and local governments to implement the priorities of migration policy, regulation of the number and quality of labor in the country by introducing appropriate legal, economic, fi nancial, organizational, informational and social activities. The system of subjects of state regulation of migration processes in Ukraine can be divided to: subjects of general regulation of migration processes and public administration bodies that directly regulate migration processes in Ukraine.The subject of counteraction to illegal migration is the bearer of the rights and obligations provided by administrative and legal norms concerning counteraction to illegal migration and is capable to realize the given rights, and to carry out the assigned duties. Migration is becoming an important factor in the development, fi ght against poverty, and the achievement of the UN Millennium Development Goals. However, the governments of many countries are unable to take advantage of the opportunities provided by migration. These include Ukraine, where the formation of state migration policy, as well as its institutional support, is still not completed.

Отмечено, что на сегодняшний день реализация государственной политики в сфере незаконной миграции имеет много пробелов. Украина как государство столкнулась с отсутствием эффективной системы правового регулирования миграционных процессов, которые создают угрозу в стране, способствуют росту преступности и образованию организованных преступных групп, обуславливают обострение социального напряжения в обществе. Определены задачи и функции субъектов противодействия нелегальной миграции. Исследованы вопросы видов субъектов противодействия нелегальной миграции в Украине, их функции и взаимное сотрудничество.
Новіченко, А. В. Суб'єкти протидії нелегальній (незаконній) міграції в Україні / Новіченко Андрій Васильович // Наше право. - 2020. - № 2. - С. 99-105. - DOI:10.32782/NP.2020.2.15.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; міграція; migration; миграция; нелегальна міграція; illegal migration; нелегальная миграция; незаконна міграція; протидія нелегальній міграції; opposition is illegal migration; противодействие нелегальной миграции; суб’єкти протидії нелегальній (незаконній) міграції; subjects of combating illegal (illegal) migration; субъекты противодействия нелегальной (незаконной) миграции; міграційна політика; migration policy; миграционная политика; державне регулювання міграції; state regulation of migration; государственное регулирование миграции